エイセイ データ ニヨル ナンキョク ノ クモ ブンプ - 山内, 恭; ヤマノウチ, タカシ; Yamanouchi , Takashi (1997)
P(論文) 南極域の気候を支配する上で重要な要因となっている雲の分布について, 衛星データを使った解析を紹介した。昭和基地で受信されたNOAA衛星のAVHRRデータのうち赤外域の三つのチャンネル, チャンネル3 (3.7μm), チャンネル4 (10.8μm), チャンネル5 (12.0μm)のデータを使ったものである。各チャンネルの輝度温度の差が雲の有力な情報となっていることが示され, この輝度温度差から検知された雲量が導出された。沿岸域をはさんで, 大陸上と海上で雲量に大きな違いがあることが分かった。昭和基地での地上観測からの雲量で検証したところ, 夏期は, チャンネル3と4の差から求めた雲量がよい一致を示したが, 夏, 冬通じて, チャンネル4と5の差から求めた雲量は不十分な結果であった。さらに, チャンネル4と5の輝度温度差とチャンネル4の輝度温度の相関関係から, 雲検知の情報が増強され, 東南極における1年間にわたる広域の雲分布が導出され, 雲の分布特性が議論された。 Analyses of cloud distribution in the Antarctic using satellite data were reported. Data of three NOAA AVHRR channels, channels 3 (3.7μm), 4 (10.8μm) and 5 (12.0μm), received at Syowa Station, were used for the analyses. Brightness temperature differences of those channels were shown to be effective to detect clouds, and cloud amounts thus detected were derived for the area around Syowa Station. A large difference was found between the cloud amount over the continental ice sheet and that over the ocean. Compared to the cloud amounts determined from the surface measurements, cloud amounts from the temperature difference between channels 3 and 4 in summer showed good agreement; however, cloud amounts from channel 4 and 5 in summer and winter showed only vague agreement. Aided from the correlation coefficient between the brightness temperature difference between channels 4 and 5,and the brightness temperature of channel 4,cloud distributions over East Antarctica throughout the year were derived, and distribution characteristics were discussed. departmental bulletin paper